Venezuelan families approaches to digital culture around the Cainama Educativo project - Montoya González, Yaimar Del Valle (2019)
The Canaima Educativo project supplied laptops (canaimitas) to Venezuela’s public schools. Although family integration was among the project’s objectives, there were not guidelines on how to achieve such objective. This research aimed to interpret how families used the canaimitas considering the importance to include digital technologies in daily life, since our society is living in a digital culture. Therefore, public policies should provide support from a broad and inclusive perspective. We used an ethnographic qualitative methodology with a hermeneutic approach. Fieldwork was performed at two high schools located in the state of Vargas. Four (4) students and their families were selected using online surveys and participated in focus group interviews. The information was organized through a textual discourse analysis using the ATLAS.ti software. The research results showed the lack of support to include the canaimitas to those families’ homes. In this sense, the members of such families approach to the digital culture with spontaneous and dynamic practices according to their own interests.